2014
DOI: 10.1021/cg5000414
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Growth of Strain-Free Magnetite Nanocrystals via Temperature-Driven Dewetting

Abstract: Temperature-driven dewetting of a self-template layer has been exploited to spontaneously grow epitaxial magnetic Fe 3 O 4 nanocrystals by pulsed laser deposition. A 10 unit cell thick Fe 3 O 4 template layer was deposited at 400 °C on a perovskite SrTiO 3 (001) substrate, followed by heating at 1100 °C, which induced dewetting of the Fe 3 O 4 template layer, forming three-dimensional islands that were uniformly distributed over the substrate surface area. These islands were used as seed crystals for the growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 54 publications
0
13
0
Order By: Relevance
“…Tb x Y 2– x O 3 composition-gradient films were deposited on wet-etched SrTiO 3 (001) substrates (Shinkosya, 5 × 10 mm 2 ) , using combinatorial PLD. A sample holder was heated using an infrared semiconductor laser. , During the growth, the substrate temperature was maintained at 600 °C. Ceramic targets of Y 2 O 3 and Tb 0.5 Y 1.5 O 3 (TOSHIMA Manufacture Co. Ltd.) were alternately ablated with fourth-harmonic (266 nm) pulses from an Nd:YAG laser (LOTIS LS-2145N/4) ,, at a pulse rate of 10 Hz and a fluence of 2.3 J/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Tb x Y 2– x O 3 composition-gradient films were deposited on wet-etched SrTiO 3 (001) substrates (Shinkosya, 5 × 10 mm 2 ) , using combinatorial PLD. A sample holder was heated using an infrared semiconductor laser. , During the growth, the substrate temperature was maintained at 600 °C. Ceramic targets of Y 2 O 3 and Tb 0.5 Y 1.5 O 3 (TOSHIMA Manufacture Co. Ltd.) were alternately ablated with fourth-harmonic (266 nm) pulses from an Nd:YAG laser (LOTIS LS-2145N/4) ,, at a pulse rate of 10 Hz and a fluence of 2.3 J/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…We speculate that higher-order matching takes place; for example, 8 × a of the Mn 2 Mo 3 O 8 film (46.40 Å) has good matching with (17/√3) × a of Al 2 O 3 (46.72 Å) with a mismatch of 0.7% (Figure S3). Such higher-order lattice matching is also observed in ZnO films on Al 2 O 3 (001) substrates and Fe 3 O 4 films on SrTiO 3 (001) substrates. , …”
Section: Resultsmentioning
confidence: 56%
“…Such higherorder lattice matching is also observed in ZnO films on Al 2 O 3 (001) substrates and Fe 3 O 4 films on SrTiO 3 (001) substrates. 19,20 We evaluated the valence states of Mo and Mn ions in the Mn 2 Mo 3 O 8 film using XPS and XAS measurements. Figure 3a shows the Mo 3d spectrum of the film.…”
Section: Methodsmentioning
confidence: 99%
“…For example, it has been reported that the maximum achievable piezoelectric strain in epitaxial Pb­(Zr, Ti)­O 3 (PZT) films deposited on the SrTiO 3 substrates is much smaller than that in bulk crystals . The substrate problem can be mitigated by thinning the substrate during device fabrication and using a cantilever design , or by forming self-standing nanostructures in which strain can be decoupled from the substrate. These problems are not unique for piezoelectric films but affect various other film materials such as magnetostrictive materials and shape memory alloys. , …”
Section: Introductionmentioning
confidence: 99%